Wind pressure acting on greenhouses: A review - Wang, Cong; Nan, Bo; Wang, Tieliang; Bai, Yikui; Li, Yuqing (International Journal of Agricultural and Biological Engineering, 2021)
Greenhouses are widely used in agricultural and horticultural production. With the characteristics of lightweight, small stiffness and high flexibility, greenhouses are sensitive to wind loads. In the calculation of wind loads, the wind pressure coefficient (Cp) is essential. The rationality of the value directly affects the safety and economy of greenhouses. Therefore, the Cp values estimation is one of the most important issues in the design of greenhouses. In order to make full use of the existing research results, in this study, three main methods for estimating Cp values were analyzed, namely, full-scale field experiment, wind tunnel experiment and numerical simulation. Five factors influencing the Cp values were then reviewed including greenhouse design parameters, greenhouse group, overhanging eaves, ventilation and wind direction. Based on the existing researches, suggestions for future development and research work were also put forward. Owing to the flexibility and deformability of greenhouses, the fluid-solid coupling method should be used to analyze the effects of vibrations on wind pressures. The interaction of building parameters (such as the number of spans, ridge height, roof shape and slope angle) and terrain around the greenhouse should be taken into consideration comprehensively. The destructive vortices occurred on the greenhouse should be further investigated.Keywords: computational fluid dynamics, greenhouse, wind pressure coefficients, wind tunnel, influence factorsDOI: 10.25165/j.ijabe.20211402.5261Citation: Wang C, Nan B, Wang T L, Bai Y K, Li Y Q. Wind pressure acting on greenhouses: A review. Int J Agric & Biol Eng, 2021; 14(2): 1–8.